Cyclosporine in Dry Eye: A Review - Gupta, Suruchi (International Journal of Medical Research and Review, 2015)
Dry eye syndrome (DES) is a multifactorial diseases with varying prevalence affecting great chunk of population worldwide. Various environmental, nutritional, hormonal and external factors altering the functional integrity of the ocular surface components have been implicated. The imbalance results in changes in epithelium causing desiccation and setting up an inflammatory cascade which causes dysregulation of the ocular surface regeneration system. With increasing knowledge of the etiology and mechanisms involved in the development of dry eye, role of cyclosporine A has been well established with numerous clinical studies. This has led to the US Food and Drug Administration (FDA) approval of the drug for the treatment of dry eye. This article reviews the pathology of development of dry eye, pharmacology of cyclosporine, use of cyclosporine A in dry eye established via various animal and clinical studies.